A high blood eosinophil count may be a risk factor for incident asthma in population at risk. (May 2019) - Bai, Chenxiao; Jiang, Di; Wang, Liwen; Xue, Fuzhong; Chen, Ou
Abstract: Background: Eosinophilia is considered to be associated with allergic disease and may predict asthma exacerbation. Eosinophils contribute to the pathophysiology and pathogenesis of asthma. However, studies on high blood eosinophil counts (BECs) and incident asthma remain scarce. Objective: To examine whether high BECs are positively associated with incident asthma in adults. Methods: Our study included 57975 participants aged from 20 to 79 years from the Shandong multi-center health check-up longitudinal study for Health Management. All patients with determined baseline BECs were ≥20 years old and free from asthma. We defined incident asthma as self-reported new-onset asthma occurring during the 10-year follow-up period. Multivariate modeling employed Poisson regression and Cox proportional hazards models to verify the association between BEC and incident asthma by adjusting demographics and some relevant comorbidities (rhinitis, nasal polyps, pneumonia, bronchitis, and chronic obstructive pulmonary disease). Results: A BEC ≥110 cells/μL was a risk factor for incident asthma (adjusted IRR = 1.62, 95% CI: 1.05–2.50, P  = .028) in the Poisson regression. In the Cox proportional hazards model, the BEC cutoff point for incident asthma was also determined to be 110 cells/μL (HR = 1.59, 95% CI: 1.01–2.51, P  = .045). Conclusion: A high BEC is a risk factor for incident asthma, especially when the BEC exceeds 110 cells/μL. This suggests that adults with high BECs are more likely to develop asthma. Highlights: High blood eosinophil counts can predict incident asthma cases. The association between BEC and incident asthma was significant when BEC cutoff points increased from 110 cells/μL. Age (>40 years), sex (female), and the presence of asthma-like diseases can help assess the risk of future asthma onset.